Physiological Responses and Agronomic Characters of Local Rice (Oryza sativa L.) Varieties from Rokan Hilir to Salinity (NaCl) Stress - Pujiati, Sri; Adiwirman, Adiwirman; Herman, Herman (Jurnal Biologi Tropis, 2025)
Rokan Hilir District, tidal swamp areas have potential for rice cultivation but often experience rising salinity due to seawater intrusion. This study aimed to analyze the physiological responses and agronomic characteristics of two local varieties, Sigudang and Sikuning, under different salinity levels, and to identify inter-parameter relationships associated with varietal tolerance. The experiment using a Completely Randomized Design (CRD) with two factors: local rice varieties (Sigudang and Sikuning) and four salinity levels (0, 2500, 5000, and 7500 ppm), each replicated five times. Data were analyzed using ANOVA at the 5% level, followed by the BNJ test at 5%, and correlation analysis to determine relationships among parameters. The results of the study showed that salinity stress had a significant effect on almost all physiological parameters and agronomic traits, with reductions at the highest salinity level ranging from 22-76%. Correlation analysis revealed very strong relationships (r > 0,80) between physiological parameters and agronomic traits, indicating that reductions in physiological function due to salinity directly contribute to decreased growth and yield. Conversely, days to maturity showed negative correlations with most parameters, indicating that prolonged maturity reflects a stress response rather than an indicator of tolerance.